Organization of Passenger Transport in the City of Andijan, Taking into Account the Environmental Factor - Zakirovich, Nasirov Ilham; ugli, Mamirjonov Sanjarbek Akmaljon (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
This paper examines the organization of passenger transport in Andijan, Uzbekistan with a specific focus on environmental sustainability. Andijan faces serious transportation challenges including traffic congestion, air pollution from old vehicles, and inadequate public transit options. The introduction provides background on Andijan's geography, population growth, economy, and transportation issues. The methods and literature review summarize research on sustainable transportation planning, public transit systems, electric vehicles, non-motorized transit, and transportation demand management. The results analyze Andijan's current transportation mode split between private automobiles, public transit, walking, and cycling. The discussion makes recommendations for improving sustainability through investments in public transit, promotion of electric vehicles, better infrastructure for non-motorized transit, congestion charges, and changes to land use policies. The conclusion summarizes the key findings and proposes an integrated sustainable passenger transport strategy for Andijan combining multiple intervention approaches.